A new giant velvet worm from Costa Rica suggests absence of the genus Peripatus (Onychophora: Peripatidae) in Central America - Barquero González, José Pablo (2020)
Introduction: Neotropical onychophoran taxonomy and diversity has been poorly investigated. Recent studies have discovered problems in species classification: they have questioned the accepted genera and the actual number of species. This is true in Costa Rica, where several unidentified species have been reported. Objective: The objective of this investigation was to evaluate the occurrence of the accepted genera in this country, and to describe a new genus and species from Central America. Methods: In 2017, we collected one onychophoran in the Keköldi Indigenous Reserve in Talamanca, Limón, Costa Rica. The specimen gave birth to several offspring. Therefore, seven organisms were analyzed. Light microscopy was used to observe the gross morphology in all samples. The detailed morphology was studied in the biggest specimen with scanning electron microscopy; after that, we performed a phylogenetic analysis with the corresponding sequence of COI. Results: According to our results, a new genus and species of giant onychophoran was found. The genus was identified by its giant size, apical piece of seven scale ranks, large conical primary papillae, dorso-median furrow flanked by two-three accessory papillae, the absence of hyaline organs and a marked sexual dimorphism with respect to the number of legs. The new species presents a particular head pattern, as well as novel structures like cephalic papillae, accessory papillae with rudimentary apical pieces, and a lack of antennal chemoreceptors. Phylogenetic analysis rendered our genus as monophyletic and includes Peripatus solorzanoi, which is grouped within the Central American clade. As our species is clustered inside the Costa Rica-Panamanian group, it is not related to the Caribbean Island nor Guyanan Shield samples, home of Epiperipatus and Peripatus respectively. Therefore, we suggest that those genera do not occur in Central America, and a new genus exists: Mongeperipatus, gen. nov. Conclusion: We concluded that Costa Rica is home to a diversity of undescribed onychophorans that requires specific studies to help clarify the taxonomy and evolutionary relationships of the group to justify their protection.